Large and Small Cerebral Vessel Involvement in Severe COVID-19: Detailed Clinical Workup of a Case Series. Issue 12 (December 2020) - Keller, Emanuela; Brandi, Giovanna; Winklhofer, Sebastian; Imbach, Lukas L.; Kirschenbaum, Daniel; Frontzek, Karl; Steiger, Peter; Dietler, Sabeth; Haeberlin, Marcellina; Willms, Jan; Porta, Francesca; Waeckerlin, Adrian; et al.
Abstract : Background and Purpose: Case series indicating cerebrovascular disorders in coronavirus disease 2019 (COVID-19) have been published. Comprehensive workups, including clinical characteristics, laboratory, electroencephalography, neuroimaging, and cerebrospinal fluid findings, are needed to understand the mechanisms. Methods: We evaluated 32 consecutive critically ill patients with COVID-19 treated at a tertiary care center from March 9 to April 3, 2020, for concomitant severe central nervous system involvement. Patients identified underwent computed tomography, magnetic resonance imaging, electroencephalography, cerebrospinal fluid analysis, and autopsy in case of death. Results: Of 32 critically ill patients with COVID-19, 8 (25%) had severe central nervous system involvement. Two presented with lacunar ischemic stroke in the early phase and 6 with prolonged impaired consciousness after termination of analgosedation. In all but one with delayed wake-up, neuroimaging or autopsy showed multiple cerebral microbleeds, in 3 with additional subarachnoid hemorrhage and in 2 with additional small ischemic lesions. In 3 patients, intracranial vessel wall sequence magnetic resonance imaging was performed for the first time to our knowledge. All showed contrast enhancement of vessel walls in large cerebral arteries, suggesting vascular wall pathologies with an inflammatory component. Reverse transcription-polymerase chain reactions for SARS-CoV-2 in cerebrospinal fluid were all negative. No intrathecal SARS-CoV-2-specific IgG synthesis was detectable. Conclusions: Different mechanisms of cerebrovascular disorders might be involved in COVID-19. Acute ischemic stroke might occur early. In a later phase, microinfarctions and vessel wall contrast enhancement occur, indicating small and large cerebral vessels involvement. Central nervous system disorders associated with COVID-19 may lead to long-term disabilities. Mechanisms should be urgently investigated to develop neuroprotective strategies. Abstract : Supplemental Digital Content is available in the text.